Upaya Meningkatkan Disiplin Guru Dalam Kehadiran Mengajar Di Kelas Melalui Penerapan Reward And Punishment Di SDN 06 Arga Makmur - Kamat Kamat (Jurnal Georafflesia: Artikel Ilmiah Pendidikan Geografi, 2017)
Improving the quality of learning in schools is highly dependent on several factors. Critical factors include the application of school culture towards quality improvement. School culture is a positive thing that must be maintained and implemented by all citizens of the school without feeling compelled. School culture that must be maintained one of them is the discipline, including the discipline of teachers in the classroom presence in the learning process. To improve the discipline of teachers can be pursued through a variety of ways. In the School Action Research (SAR), attempted action in the form of application of Reward and Punishment for teachers at SD Negeri 06 Arga Makmur, North Bengkulu Regency. This study was conducted in two cycles, teacher discipline in the presence of the classroom in the learning process increased and meet the predefined indicator of 75%. From the results of this study, it can be concluded that to improve teacher discipline in attendance in the classroom on teaching and learning activities can be done with the application of Eward and Punisment to the teacher.